GOOD CORPORATE GOVERNANCE SEBAGAI WUJUD PERAN DEWAN PENGAWAS SYARIAH DAN DEWAN SYARIAH NASIONAL DI PERBANKAN SYARIAH - Nur Kholisah; Nia Amellia; Sukma Purbaningrum; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
The development of Islamic financial institutions in Indonesia requires the alertness of DSN-MUI in solving the problems that occur, especially related to product innovation needed by the community. Therefore, DSN-MUI has affiliated parties that will provide their services to Sharia banks or Sharia Business Units (UUS) in ensuring the implementation of Sharia principles in Islamic banking activities in Indonesia, namely the Sharia Supervisory Board (DPS) and the National Sharia Council (DSN). The research method used in this research is a library research method with a qualitative descriptive approach. With the use of the literature study data collection method or library research, the author does not need to go directly to the field for data collection, but only by taking various supporting reference sources, be it online references or books to support the writing of this article. The result of this research is that the author and readers can find out how the implementation of the Sharia Supervisory Board (DPS) and the Sharia National Board (DSN) in realizing Good Corporate Governance (GCG) in Islamic banking in Indonesia.